IMPLEMENTASI PASAL 61 AYAT (3) PP NOMER 24 TAHUN 1997 KAITANNYA DENGAN TENGGANG WAKTU PENDAFTARAN HAK MILIK ATAS TANAH KARENA PEWARISAN DI SAMARINDA - Meliyana Meliyana (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACSBased on Article 61 paragraph 3 of Government Regulation Number 24 of 1997 statedthat: If a person who has right stoland has passed away then the right as an heir is obliged to register his right with in 6 (six) months since the death of that person, shall not be charged Registration.From the provisions of the above article that with the existence of legal events in the form of in heritance, it can be said that the heirs who receive the transfer of owner ship rights as heirs must register the transfer of rights to the Office of National Defense.Within a period of 6 (six) months from the date of the death of the heir it shall be registered,it is intended to be issued a new certificate in the name of the heirs concerned and so that the heirs certainty and legal protection for the new holder of property rights.The registration of transfer of rights due to in heritance is done directly by the right holder / heir to the National Land Office accompanied by documents that must be fullfilled that the respondent who register the transfer of owner ship rights because the in heritance is done through the lurah as much as 18 respondents or 60% who make the request Through notary services as much as 9 respondents or 27% and who register the transfer of rights due to individual in heritance as much as 7 respondents or 19%.